Does phosphogypsum application affect salts, nutrients, and trace elements displacement from saline soils? - Outbakat, M Barka; Choukr-Allah, Redouane; EL Gharous, Mohamed; EL Omari, Kamal; Soulaimani, Aziz; EL Mejahed, Khalil (Frontiers in Environmental Science, 2022)
Salinity and sodicity are the most agricultural challenges in arid and semi-arid regions. A pot experiment was undertaken, to evaluate the effect of Phosphogypsum (PG) and Gypsum (G), to remove salts, nutrients and trace elements in leached water from saline and saline-sodic soils. In order to determine the efficiency and safety of these amendments, as an affordable strategy, for overcoming salinity and sodicity stress. The PG at 0, 15, 30 and 45 t/ha and G at 15 t/ha were mixed with the upper 9 cm soil in the pot before being leached. The soils were collected from Sed El Masjoune and Sidi El Mokhtar areas of morocco with ECe of 140.6 mS/cm and 11.7 mS/cm respectively. The highest doses of PG (≥30 t/ha) removed significant amount of salts and nutrients. Calcium sulfate supplies calcium ions to replace salt ions (sodium, especially). The replaced salts are leached from the soil. The PG was more efficient compared to G in terms of salts leaching. Quantities of trace elements in the leachate, for most analyzed elements, were below the recommended limits of drinking and irrigation water. Because the experiment’s alkaline conditions (basic water and soil) reduce the solubility and mobility of trace elements. The amendment application did not affect saturation index (SI) of the main minerals. However, water passing through the soil increased the SI. which could result in groundwater mineral precipitation.